Implementasi Agile Organization di Sektor Publik: Studi Kasus Kementerian Energi dan Sumber Daya Mineral - Prasojo, Hendris Agung; Aswad, Muhammad; Utoro, Bambang (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2025)
This research aims to identify the variables influencing the success of organisasi agile implementation in the Ministry of Energy and Mineral Resources (KESDM), thereby developing a conceptual framework for agile implementation in the Ministry of Energy and Mineral Resources (KESDM).Through this research, it can be determined the readiness of the Ministry of Energy and Mineral Resources (KESDM) in implementing organisasi agile and identify ways to overcome its challenges, thus making the transition process from waterfall system to agile system smoother. The researcher utilizes a mixed-method approach, combining literature review as a qualitative method followed by measurement using quantitative method.From the literature review, a conceptual framework for organisasi agile implementation in the public sector is developed, consisting of variables such as leadership identity, process & value creating, strategy, structure, and technology, which is then used to measure the maturity level of agile implementation readiness. The measurement results indicate that the Ministry of Energy and Mineral Resources (KESDM) is positioned at a level of "defined and improved," with the technology variable scoring 4.039, followed by strategy, leadership identity, process, value creating, and structure. The "defined and improved" position implies that agile implementation in the Ministry of Energy and Mineral Resources (KESDM) still requires improvement to reach the sustain position.Based on the findings of this research, it is hoped that the Ministry of Energy and Mineral Resources (KESDM) will continue to enhance the implementation of organisasi agile practices, thereby improving its services to all stakeholders.Â Â